Linked Conservation Data: Driving Change in Documentation Practice. (10th August 2022) - Velios, Athanasios; St John, Kristen
ABSTRACT: Documentation is a core task for conservators, allowing evaluation of past choices and providing an evidence base for reasoned decision-making for future practice. However, much of the documentation created is not shared with other conservators or broader audiences. During the Linked Conservation Data (LCD) project, we explored the potential of documentation practices known as Linked Data for conservation, inspired by practices in other domains including medical science and biology, as well as various openGLAM initiatives. As part of the project, we developed: guidelines for harmonising disparate conservation terminologies; proposals for encoding different types of conservation data; a template for articulating policy in relation to conservation data; and a Linked Data pilot demonstrating the value of the approach. This work encourages institutions to begin sharing conservation records routinely, for use and re-use by other conservators. Adopting such a practice at large scale will provide an invaluable resource of conservation-related information that can be used for decision-making and enable data analysis and statistical work with large samples in conservation. We present conclusions and lessons learned from the LCD pilot, including the: importance of structured records; role of documentation of conservation vocabularies; foundational work still needed for sharing records as Linked Data; and practicalities of implementing a Linked Data system for sharing conservation records. We conclude by outlining the role and responsibilities that professional bodies need to adopt towards this effort.